ENHANCING BASIC LITERACY THROUGH INTERACTIVE LEARNING MEDIA AND ENJOYABLE AT KB AN NUR MUTTAQIN - Karlina, Nichi Hana; Sarifiyono, Aggi Panigoro; Budiman, Budiman; Rd. Zidni Rizan Al-Zhahir Yanuar; Hernawan, Kartika Nursyabanita (LPPM Universitas Bina Bangsa, 2024)
This Community Service Program addresses the low literacy skills among early childhood students at KB A Nur Muttaqin, where about 60% of children struggle with reading and writing. Contributing factors include the lack of interactive teaching methods and limited learning materials. Teacher and parent involvement in the literacy process is also minimal. The program aims to improve literacy through interactive learning media, physical and digital libraries, and training for teachers and parents. The methods used are Participatory Action Research (PAR) and Asset-Based Community Development (ABCD), focusing on participation and local resources. Key activities include media development, library setup, and training. The program seeks a 20% increase in children's literacy skills, 80% improvement in teachers' competence using media, and enhanced parental literacy awareness. Early results show increased reading interest and greater parental engagement.